A model for clinical evaluation - M. Mulder (AOSIS, 1992)
After grappling for years with the problems associated with clinical evaluation In nursing, and becoming increasingly am re of the importance of this aspect of the clinical teaching process, the researcher resolved to make an indepth study of the state of clinical evaluation in nursing. The study was undertaken in the second semester of1990.